Linking morphodynamic response with sediment mass balance on the Colorado River in Marble Canyon: Issues of scale, geomorphic setting, and sampling design. Issue 2 (4th April 2013) - Grams, Paul E.; Topping, David J.; Schmidt, John C.; Hazel, Joseph E.; Kaplinski, Matt
Abstract: [1] Measurements of morphologic change are often used to infer sediment mass balance. Such measurements may, however, result in gross errors when morphologic changes over short reaches are extrapolated to predict changes in sediment mass balance for long river segments. This issue is investigated by examination of morphologic change and sediment influx and efflux for a 100 km segment of the Colorado River in Grand Canyon, Arizona. For each of four monitoring intervals within a 7 year study period, the direction of sand‐storage response within short morphologic monitoring reaches was consistent with the flux‐based sand mass balance. Both budgeting methods indicate that sand storage was stable or increased during the 7 year period. Extrapolation of the morphologic measurements outside the monitoring reaches does not, however, provide a reasonable estimate of the magnitude of sand‐storage change for the 100 km study area. Extrapolation results in large errors, because there is large local variation in site behavior driven by interactions between the flow and local bed topography. During the same flow regime and reach‐average sediment supply, some locations accumulate sand while others evacuate sand. The interaction of local hydraulics with local channel geometry exerts more control on local morphodynamic response than sand supply over an encompassing river segment. Changes in the upstream supply of sand modify bed responses but typically do not completely offset the effect of local hydraulics. Thus, accurate sediment budgets for long river segments inferred from reach‐scale morphologic measurements must incorporate the effect of local hydraulics in a sampling design or avoid extrapolation altogether. Key Points: Local hydraulics more important than sediment supply at reach scale Morphologic measurements cannot be extrapolated to track sediment supply Sand storage in Marble Canyon was stable or increased between 2002 and 2009